Kewenangan Pengadilan Agama dalam Menyelesaikan Perceraian Nikah Campuran - Mochammad Rohman Antoni; Imam Suroso (Pusat Riset dan Inovasi Nasional, 2024)
Every country has legal regulations governing marriage in an effort to create a clear legal basis for its implementation. Regulations regarding marriage in Indonesia in general and as a whole are regulated by Law Number 1 of 1974 concerning Marriage. Overall, Law Number 1 of 1974 concerning Marriage covers aspects relating to the requirements, procedures and rights inherent in couples who have legally entered into a marriage. Article 57 of the Marriage Law regulates mixed marriages, which are defined as marriages between two people who are subject to different laws in Indonesia because of their different nationalities. Divorce can occur in marriages, including mixed marriages. Divorce in a mixed marriage means a divorce that occurs between a husband and wife, one of whom is an Indonesian citizen (WNI) and the other is a foreign citizen (WNA). The laws and regulations governing mixed divorce are Law Number 1 of 1974 concerning Marriage and Law Number 12 of 2006 concerning Citizenship. In this research, examples of mixed divorce cases between Indonesian citizens and foreign citizens will be taken by studying the Putusan PA DENPASAR Nomor 406/Pdt.G/2020/PA.Dps which was decided at the Denpasar Religious Court, Denpasar City, Bali Province.